Expression Of Cardinal Numbers in The Holy Qur'an - Akhrorov Ivadulla Ziyatovich (Zien Journals, 2021)
The following article provides a brief and theoretical look at the Qur'an, which is based on divine proportions, one can see specific laws and grammatical bases in the use of numbers, including cardinal numerals and the laws and norms identified during our study through examples
Keywords: decimals in Arabic; complex numbers; feminine; masculine